Identifikasi Keberadaan Akuifer Air Tanah Menggunakan Metode Geolistik Vertical Electrical Sounding (VES) di Padukuhan Dondong, Kalurahan Jetis, Kapanewon Saptosari, Kabupaten Gunung Kidul - Dwika Miftahul Qohar; Vincentia Trisna Yoelinda; Riki Pratama; Elbert Felix Arthur Tampubolon (Direktorat Pengabdian kepada Masyarakat, 2024)
PDAM clean water services cannot provide access to all communities in Kelurahan Jetis, Kecamatan Saptosari, Kabupaten Gunung Kidul, so that the poor only rely on rainfed systems and utilize the lake. The purpose of this study was to determine the lithology of rocks in the research location and the potential existence of groundwater aquifers through Geolistrik VES (Vertical Electrical Sounding) Schlumberger configuration data. The results of this study indicate that based on VES geoelectric measurements in Padukuhan Dondong, Kelurahan Jetis, Kecamatan Saptosari, there are 6 layers at point A and point B with limestone lithology dominated. The resistivity analysis results show that the potential groundwater aquifer is at a depth of 14.89 - 30.25 meters with a resistivity value of 14.32 (Ωm) at point A and 36.47 - 64.94 meters with a resistivity value of 36.26 (Ωm) at point B. The results of this VES geoelectric experiment are in accordance with the results of groundwater well drilling at point A.